Exposure of Free-Ranging Wild Animals to Zoonotic Leptospira interrogans Sensu Stricto in Slovenia - Diana Žele-Vengušt; Renata Lindtner-Knific; Nina Mlakar-Hrženjak; Klemen Jerina; Gorazd Vengušt (Animals, 2021)
A total of 249 serum samples from 13 wild animal species namely fallow deer (Dama dama, n = 1), roe deer (Capreolus capreolus, n = 80), red deer (Cervus elaphus, n = 22), chamois (Rupicapra rupicapra, n = 21), mouflon (Ovis musimon, n = 4), brown hare (Lepus europaeus, n = 2), nutria (Myocastor coypus, n = 1), red fox (Vulpes vulpes, n = 97), stone marten (Martes foina, n = 12), European badger (Meles meles, n = 2), golden jackal (Canis aureus, n = 2) Eurasian lynx (Lynx lynx, n = 2) and grey wolf (Canis lupus, n = 3) were analysed for the presence of antibodies against Leptospira interrogans sensu stricto. Serum samples were examined via the microscopic agglutination test for the presence of specific antibodies against Leptospira serovars Icterohaemorrhagiae, Bratislava, Pomona, Grippotyphosa, Hardjo, Sejroe, Australis, Autumnalis, Canicola, Saxkoebing and Tarassovi. Antibodies to at least one of the pathogenic serovars were detected in 77 (30.9%; CI = 25–37%) sera. The proportion of positive samples varied intraspecifically and was the biggest in large carnivores (lynx, wolf and jackal; 86%), followed by mezzo predators: stone marten (67%) and red fox (34%), and large herbivores: red deer (32%), roe deer (25%), alpine chamois (10%) and mouflon (0%). Out of the 77 positive samples, 42 samples (53.8%) had positive titres against a single serovar, while 35 (45.4%) samples had positive titres against two or more serovars. The most frequently detected antibodies were those against the serovar Icterohaemorrhagiae. The present study confirmed the presence of multiple pathogenic serovars in wildlife throughout Slovenia. It can be concluded that wild animals are reservoirs for at least some of the leptospiral serovars and are a potential source of leptospirosis for other wild and domestic animals, as well as for humans.